2015
DOI: 10.1016/j.devcel.2015.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Somatic Cell Encystment Promotes Abscission in Germline Stem Cells following a Regulated Block in Cytokinesis

Abstract: SUMMARY In many tissues the stem cell niche must coordinate behavior across multiple stem cell lineages. How this is achieved is largely unknown. We have identified delayed completion of cytokinesis in germline stem cells (GSCs) as a mechanism that regulates the production of stem cell daughters in the Drosophila testis. Through live imaging, we show that a secondary F-actin ring is formed through regulation of Cofilin activity to block cytokinesis progress after contractile ring disassembly. The duration of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
96
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 60 publications
(110 citation statements)
references
References 39 publications
5
96
0
Order By: Relevance
“…Overall, a direct relationship between cleavage orientation and fate determination remains unclear. Moreover, inheritance of additional asymmetric factors aside from the apical membrane, such as the mother centrosome Paridaen et al, 2013), the basal process (Tsunekawa et al, 2012), or the midbody (Ettinger et al, 2011;Kuo et al, 2011) have been reported to influence fate specification.…”
Section: Regulation Of Cytokinesis and Control Of Cortical Developmentmentioning
confidence: 99%
See 4 more Smart Citations
“…Overall, a direct relationship between cleavage orientation and fate determination remains unclear. Moreover, inheritance of additional asymmetric factors aside from the apical membrane, such as the mother centrosome Paridaen et al, 2013), the basal process (Tsunekawa et al, 2012), or the midbody (Ettinger et al, 2011;Kuo et al, 2011) have been reported to influence fate specification.…”
Section: Regulation Of Cytokinesis and Control Of Cortical Developmentmentioning
confidence: 99%
“…Cleavage is often approximately perpendicular to the apical membrane (Noctor et al, 2008). A prevailing hypothesis holds that asymmetric neurogenic divisions result from unequal inheritance of apical membrane or junctions due to unequal cleavage of the apical membrane (Kosodo et al, 2004;Marthiens and ffrenchConstant, 2009). This is analogous to Drosophila neuroblasts, where a 90-degree change in cleavage angle determines whether one or both daughters inherit the apical membrane (Rhyu et al, 1994;Chenn and McConnell, 1995).…”
Section: Regulation Of Cytokinesis and Control Of Cortical Developmentmentioning
confidence: 99%
See 3 more Smart Citations